UTILIZATION OF ANTENATAL CARE SERVICES AMONG REFUGEE TEENAGE MOTHERS AT NAKIVALE REFUGEE SETTLEMENT IN WESTERN UGANDA. A PHENOMENOLOGICAL STUDY. - Ecodu, Simon Peter; Muhumuza, Benon; Rukundo, Lydia; Kazibwe, Francis (Student’s Journal of Health Research Africa, 2023)
Introduction: Antenatal care is crucial for positive pregnancy outcomes and is dependent on the timing and quality of care. It promotes health education and helps identify and manage maternal complications and risk factors. In Sub-Saharan Africa, pregnancy complications and childbirth are the leading cause of death for women aged 10-19. This study examined teenage mothers’ experiences and perceptions of accessing and utilizing antenatal care services in the Nakivale refugee settlement, Isingiro district. Methodology: A phenomenological study was conducted on teenage mothers in Nakivale, using a snowball sampling method. Key informant interviews were conducted, lasting 45 minutes -1 hour. Ethical clearance was obtained from Bishop Stuart University REC and informed consent was obtained from participants. Data was analyzed thematically using Nvivo version 12. Results: Teenage mothers face challenges utilizing antenatal care services including negative treatment from family and community members. However, positive feelings of responsibility alleviate stress, making early mothers more resilient. Conclusions: Access to ANC services is closely linked to its utilization, but societal discrimination against teenage mothers affects ANC utilization. Teenage-friendly spaces in Nakivale significantly influenced access and utilization of ANC services. Recommendations: The study suggests establishing customized ANC services for teenage mothers in the Nakivale refugee settlement, Isingiro district, to enhance access and utilization of ANC.